Development of Flash Card Palindrome to Stimulate Critical Thinking Skills in Aged 5-6 Years - Saputri, Dinda Ananta; Harianja, Sri Indriani; Utami, Winda Sherly (Journal of English Language and Education, 2026)
This study was conducted with the aim of developing a flash card palindrome (FCPM) media as a medium to stimulate critical thinking skills in children aged 5-6 years. The background of this study is due to the low level of higher-order thinking skills in early childhood which is still evident from children's passivity when learning, a learning system that is still dominated by teachers, and the learning media used is less varied. This study uses a Research and Development (RD) approach with a 4D model that includes the stages of define, design, develop and disseminate. The subjects of this study consisted of teachers and principals in 3 kindergartens in Tambak Sari Village. In addition, data collection techniques used were interviews, documentation and questionnaires. The results of the feasibility test showed that the media obtained a score of 91% from media experts, 82% from material experts and 92% from teachers with a very good category. Limited implementation showed that children were more active in observing patterns, comparing letters and conveying simple reasons in determining palindrome words. These findings also indicate that FCPM is feasible to use and has the potential to stimulate analytical and reflective thinking skills in early childhood.